We cannot change the past, but we can change its meaning. A randomized controlled trial on the effects of self-help imagery rescripting on depression. (May 2018) - Moritz, Steffen; Ahlf-Schumacher, Jana; Hottenrott, Birgit; Peter, Ulrike; Franck, Stephanie; Schnell, Thomas; Peter, Helmut; Schneider, Brooke C.; Jelinek, Lena
Abstract: Background: Imagery rescripting is a psychotherapeutic technique that aims to ameliorate negative emotions by altering (i.e., rescripting) inner representations of negative memories and images. Although the treatment was initially developed for traumatized individuals, face-to-face interventions have yielded promising results for patients with other diagnoses as well. The present study explored the feasibility and efficacy of the approach when used as a self-help intervention for depression. Method: A total of 127 individuals with diagnosed depression were randomly allocated to either a wait-list control condition or received a brief or long version of a manual teaching imagery rescripting. Six weeks after inclusion, patients were invited to participate in the post assessment. The Beck Depression Inventory (BDI-II) served as the primary outcome (registered at ClinicalTrials.gov (NCT03299127). Results: The long version was superior to the wait-list control condition on the BDI-II, self-esteem, and quality of life at a medium effect size. No effects emerged for anxiety. No significant between-group differences were found for the brief version. Moderation analyses indicated that the self-help approach seems particularly beneficial for those scoring high on symptoms, willingness to change, and expectancy (baseline). Most patients indicated they would use the technique in the future. Discussion: The efficacy of imagery rescripting was confirmed when applied via self-help. Use of the long form of the manual is recommended. Future studies are needed to ascertain whether treatment effects are sustained over time. Highlights: Imagery rescripting (IR) improved negative emotions in face-to-face trials. Efficacy of IR as a self-help intervention in depression tested for the first time. IR led to significant improvements on depression and quality of life. The self-help technique was particularly beneficial for patients high on symptoms, willingness to change and high expectancy. Long version was more effective than abbreviated version.